Lamb Head as a New Training Model for Soft Tissue and Flap Surgery on Face - Apaydin, Fazil; Soto-Galindo, German Armando; Aydın, Bekir; Capelleras, Marta (Facial Plastic Surgery, 2025)
Training in facial soft tissue and flap surgery is limited by access to cadaver models and realistic simulation tools.This study aimed to evaluate the lamb head as a practical and cost-effective model for facial flap planning and soft tissue closure techniques in surgical education.Prospective observational study involving two dissection courses with surgical residents. Reporting complies with STROBE (STrengthening the Reporting of OBservational studies in Epidemiology) guidelines.Two lamb heads were used for initial testing. Subsequently, two training sessions were conducted with 49 ENT and dermatology residents. Participants practiced standard flap designs using predrawn templates. Postsession feedback was collected.All participants reported increased understanding and confidence. The model was rated highly for its realism and teaching value.The lamb head provides a realistic, accessible, and low-cost model for facial soft tissue training. It may be valuable for residency programs lacking access to cadaveric simulation.
Keywords: facial flap training; surgical education; lamb head model; animal dissection; reconstructive simulation